Shallow slope stability evolution during rainwater infiltration considering soil cracking state. (January 2020) - Zhang, Jian; Zhu, David; Zhang, Shihua
Abstract: Cracks in a shallow slope will increase soil infiltration capacity and sequentially affect slope stability. To further understand the evolutionary characteristics of shallow slope stability caused by rainwater infiltration considering desiccation crack extension states, a series of analyses are conducted. The ponding infiltration characteristics of rainwater in a slope at different crack extension states are analyzed based on the Green-Ampt infiltration model. The evolution of slope stability under infiltration considering the crack expansion state is discussed under non-ponding infiltration and ponding infiltration. For the unsaturated infiltration case, an increase in both soil infiltration capacity caused by cracking and rainfall intensity will cause the slope to evolve toward an "unstable" state. The factor of safety (FS) gradually approaches the threshold FS0, which is mainly controlled by soil strength parameters, bulk density, and slope inclination. Under ponding infiltration conditions, the soil cracking degree will affect water migration and further affect slope stability evolution. The crack developmental state and rainfall conditions will affect the slope water saturation state during rainwater infiltration and further affect the evolution characteristics of the factor of safety at different depths.